Rural junction: architecture bridging the gap - Pretorius, Anchen (University of the Free State, 2021)
Abstract not available
Dissertation (M.Arch. (Architecture))--University of the Free State, [2021]
Keywords: Architectural inventiveness; Training; Personal skills and the redevelopment; Unemployment rate - South Africa; Department of Statistics - South Africa